Rebooting American politics : the Internet revolution - Gainous, Jason, 1971- (Rowman & Littlefield Publishers, 2011)
"Going beyond theory and guess-based forecasts, this book systematically explores and measures the implications of the growing use of the Internet in the American political landscape. The authors show that the Internet changes the way voters process information and explain how the use of the Internet is causing a marked shift not just in who votes but in who wins. Breaking away from conjecture, the book demonstrates how the new digital world is changing the very heart of American politics."--Publisher description.